2020
DOI: 10.1101/2020.03.31.20048967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge and behaviors toward COVID-19 among U.S. residents during the early days of the pandemic

Abstract: Objective: To test the hypothesis that knowledge of COVID-19 influences participation in different behaviors including self-reports of purchasing more goods than usual, attending large gatherings, and using medical masks. Methods: Cross-sectional online survey of 1,034 U.S. residents age 18+ conducted on March 17, 2020. Results: For every point increase in knowledge, the odds of participation in purchasing more goods (OR=0.88, 95% CI:0.81-0.95), attending large gatherings (OR=0.87, 95%CI: 0.81-0.93), and using… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 13 publications
6
42
1
1
Order By: Relevance
“…The general knowledge score of the participants in this survey on COVID-19 is approximately 18.2 out of 21 total points (approximately 87%) at a time approximately 6 weeks after the first case was diagnosed on 11 March 2020 in Malaysia. Our data suggested that, generally, Malaysian residents are more knowledgeable regarding COVID-19 compared to residents in other studies such as in the USA which only scored 9.72 out of 12 points (approximately 80%) (Clements 2020). However, the current data showed a slight difference in the percentage compared to with China 10.8 out of 12 points (approximately 90%), and this could suggest that they had experience during the SARS outbreak in the 2000s (Zhong et al 2020) and the variances in measurement and scoring systems are unlikely for accurate evaluations of knowledge levels through these studies.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…The general knowledge score of the participants in this survey on COVID-19 is approximately 18.2 out of 21 total points (approximately 87%) at a time approximately 6 weeks after the first case was diagnosed on 11 March 2020 in Malaysia. Our data suggested that, generally, Malaysian residents are more knowledgeable regarding COVID-19 compared to residents in other studies such as in the USA which only scored 9.72 out of 12 points (approximately 80%) (Clements 2020). However, the current data showed a slight difference in the percentage compared to with China 10.8 out of 12 points (approximately 90%), and this could suggest that they had experience during the SARS outbreak in the 2000s (Zhong et al 2020) and the variances in measurement and scoring systems are unlikely for accurate evaluations of knowledge levels through these studies.…”
Section: Discussionsupporting
confidence: 40%
“…Promisingly, the survey finds the majority of the participants take it seriously by enhancing their protective behaviour such as wearing masks, frequent handwashing, sanitizing their hands with alcohol hand sanitizer, wearing gloves and avoiding crowded places even before the MCO had commenced (Mohd Hanafiah and Wan 2020). It was found that approximately 76% respondents from a recent study conducted in the USA showed a large population chose to ignore wearing masks (Clements 2020); on the other hand, this survey indicated that the majority of the Malaysian residents complied to those rules by wearing a mask whenever they are outside of their home. Results from this study also showed that the majority of the respondents practice social distancing (approximately 1 m) and pack their food instead of eating outside and the messages have been extensively circulated since the commencement of the MCO period (Wong and Alias 2020), and this demonstrates that Malaysians have taken these issues seriously.…”
Section: Discussionmentioning
confidence: 79%
“…In addition to lower rate face mask user, social distancing had practiced by only 10% participants which was much lower than the nding of a study conducted by John M Clements et al, USA, which was 70% peoples avoid mass gathering [17]. The difference might be due two major reasons; rstly, the variation of number of reported cases and fatality in two nations at a time of data collection; secondly, difference of two country's peoples in capacity to cop up economic burden of social distancing.…”
Section: Discussionmentioning
confidence: 65%
“…For attitudes about pandemics, worry/fear/helplessness about pandemic (13, 14, 22, 28, 31, 33, 49, 51, 52, 60, 61, 63, 65, 68, 72, 76-78, 81, 83, 84), confidence in governments' ability to manage pandemic (13,23,28,30,33,41,61,63,65,68,70,77,78,82) and perceived severity of infection as a public health problem (13,29,39,41,44,45,59,65,70,72) was most commonly assessed. (Table 3) For practices in pandemics, behaviours related to mask utilization (14,16,23,26,28,30,32,33,35,38,40,48,59,61,63,65,70,73,80,82,(84)(85)…”
Section: Themes Identified From Items Used In Health Literacy Questiomentioning
confidence: 99%